The Impacts of Perceived Advertising Spending and Price Promotions on Brand Equity: A Case of An Indonesian Instant Noodle Brand - Tamara, Steven (iBuss Management, 2014)
One of Indonesiaâs largest producers of instant noodle has the long term vision to makeÂ  its brandÂ  Indonesiaâs number one instant noodles brand. Heavy advertising and intense price promotions are part of its strategy to increase the brand equity. The researcher, therefore, wishes to examine whether advertising and price promotions that the company conducts contribute to the instant noodle brand equity. To test the impacts of perceived advertising spending and price promotions on brand equity and its dimensions (perceived quality, brand loyalty, brand awareness, brand image), a quantitative approach is employed, using 35-item, 5-point Likert scale questionnaires. All of the respondents are coming from Surabaya area, altogether 105 respondents chosen using simple random sampling method. Pearson Correlation and Multiple Regression analysis methods are used to examine the result. The result has two conclusions. First, perceived price promotions have significant positive effects on brand equity. Second, perceived advertising spending has no significant effect on brand equity. Â Keywords:Â  Perceived Advertising Spending, PerceivedÂ  Price Promotions, Brand Equity, Instant Noodle.